2008
DOI: 10.1016/s1875-4597(08)60026-0
|View full text |Cite
|
Sign up to set email alerts
|

Hemodynamic Changes During Spinal Surgery in the Prone Position

Abstract: Decreases in SV and CI are the main causes of a decrease in BP in the prone position during lumbar spinal surgery.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
27
1

Year Published

2012
2012
2022
2022

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 37 publications
(30 citation statements)
references
References 9 publications
2
27
1
Order By: Relevance
“…This suggests that baroreflex-mediated HR responses may be impaired during this period, resulting in a reduced ability to maintain MAP in the prone position, potentially reflecting reduced cardiac output. This is consistent with findings of reduced cardiac index, a measure of cardiac output relative to body surface area, in adults 47,48 and children 49 in the prone compared with the supine position. Reduced cardiac output may explain the large deficit in cerebral oxygenation seen in the prone position at 2 to 3 months CA.…”
Section: Figuresupporting
confidence: 90%
“…This suggests that baroreflex-mediated HR responses may be impaired during this period, resulting in a reduced ability to maintain MAP in the prone position, potentially reflecting reduced cardiac output. This is consistent with findings of reduced cardiac index, a measure of cardiac output relative to body surface area, in adults 47,48 and children 49 in the prone compared with the supine position. Reduced cardiac output may explain the large deficit in cerebral oxygenation seen in the prone position at 2 to 3 months CA.…”
Section: Figuresupporting
confidence: 90%
“…7À11 Reduced stroke volume and cardiac index results in a drop in blood pressure often seen when a patient is turned from supine to prone. 10 Respiratory changes include a 30% to 35% decrease in respiratory compliance and increase in peak airway pressure. 7 This in turn decreases venous return and cardiac output.…”
Section: Discussionmentioning
confidence: 99%
“…Regarding the frames, some suggested that the SV decreases when patients are placed on a convex saddle frame [6,8,12]. In the current study, a longitudinal bolster device that partially supports the chest and pelvis, partially compresses the abdomen, and positions the legs above the heart was used.…”
Section: Discussionmentioning
confidence: 95%
“…Most of the previous relevant studies showed that the SV, CI [6], and blood pressure [7,8] decrease when patients are made to assume a prone position. When a patient assumes a prone position, the arterial pressure can remain stable, but the CO usually decreases due to the reduced venous return.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation